2017
DOI: 10.1038/s41598-017-13758-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flux pinning in YBCO multilayer films with BCO nanodots and segmented BZO nanorods

Abstract: The flux pinning properties of the high temperature superconductor YBa2Cu3O7−δ (YBCO) have been conventionally improved by creating both columnar and dot-like pinning centres into the YBCO matrix. To study the effects of differently doped multilayer structures on pinning, several samples consisting of a multiple number of individually BaZrO3 (BZO) and BaCeO3 (BCO) doped YBCO layers were fabricated. In the YBCO matrix, BZO forms columnar and BCO dot-like defects. The multilayer structure improves pinning capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Above 700°C, the BaF 2 phase is reduced due to the reaction with the Y 2 Cu 2 O 5 phase to the final YBCO 6 phase. This observation corresponds to literature data and shows the reactivity of single metal oxide nanocrystals during the nucleation and growth of YBCO film. 2CuO+normalY2normalO3normalY2Cu2normalO5normalY2Cu2normalO5+2Ba(O,F)2+4CuOfalse→normalH2O2YBa2Cu3normalO7x+4HF…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Above 700°C, the BaF 2 phase is reduced due to the reaction with the Y 2 Cu 2 O 5 phase to the final YBCO 6 phase. This observation corresponds to literature data and shows the reactivity of single metal oxide nanocrystals during the nucleation and growth of YBCO film. 2CuO+normalY2normalO3normalY2Cu2normalO5normalY2Cu2normalO5+2Ba(O,F)2+4CuOfalse→normalH2O2YBa2Cu3normalO7x+4HF…”
Section: Resultssupporting
confidence: 91%
“…The nucleation and growth of TFA‐based or reduced fluorine‐based YBCO systems can be found in literature and is described as the ex situ BaF 2 process . Generally, it is reported that the formation of BaF 2 instead of BaCO 3 occurs when a fluorine content of more than 15.4% is used .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper 25 , where the validation of the molecular dynamics (MD) simulation used in this work is presented, the effect of nanorod diameter was shortly studied as a demonstration of the feasibility of the simulation, but a detailed analysis on this subject is still lacking. The simulation model has also been used in our previous work 9 to analyse critical current anisotropies in multilayer films containing both nanodots and nanorods and the effect of the splay and fragmentation of the nanorods on J c (θ)-peak in the vicinity of YBCO c-axis (c-peak) has been studied in 24 .…”
mentioning
confidence: 99%
“…Intensive research on fabrication of BZO doped YBCO films was conducted in the past [7][8][9][10][11]. However, limited study of BZO doped YBCO bulks has been reported so far [5,12].…”
Section: Introductionmentioning
confidence: 99%